2021
DOI: 10.1021/acs.inorgchem.1c02072
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and Reactivity of a Pair of Neutral and Cationic Heterobimetallic RuZn2 Complexes

Abstract: A combined experimental and computational study of the structure and reactivity of two [RuZn 2 Me 2 ] complexes, neutral [Ru(PPh 3 )(Ph 2 PC 6 H 4 ) 2 (ZnMe) 2 ] ( 2 ) and cationic [Ru(PPh 3 ) 2 (Ph 2 PC 6 H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
3
7
0
Order By: Relevance
“…Both the Ru−Zn and Ru−H bond paths show similar BCP ρ ( r ) values to those in 1 a and the computed Ru−H distances are again 1.70 Å. We have previously found delocalisation indices to be more discriminating for Ru−Zn bonding [5] and the significantly lower value computed for Ru−Zn1 suggests this Ru−Zn interaction is weakest [11] . QTAIM, ETS‐NOCV and NCI analyses again indicate that any Zn⋅⋅⋅Zn and Zn⋅⋅⋅H interactions in 2 b are weak (Supporting Information).…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…Both the Ru−Zn and Ru−H bond paths show similar BCP ρ ( r ) values to those in 1 a and the computed Ru−H distances are again 1.70 Å. We have previously found delocalisation indices to be more discriminating for Ru−Zn bonding [5] and the significantly lower value computed for Ru−Zn1 suggests this Ru−Zn interaction is weakest [11] . QTAIM, ETS‐NOCV and NCI analyses again indicate that any Zn⋅⋅⋅Zn and Zn⋅⋅⋅H interactions in 2 b are weak (Supporting Information).…”
Section: Methodssupporting
confidence: 58%
“…Both the RuÀ Zn and RuÀ H bond paths show similar BCP ρ(r) values to those in 1 a and the computed RuÀ H distances are again 1.70 Å. We have previously found delocalisation indices to be more discriminating for RuÀ Zn bonding [5] and the significantly…”
supporting
confidence: 66%
“…The topology of the electron density in the equatorial {RuZn 4 H 2 } plane of 1 a taken from a QTAIM study shows the presence of Ru−Zn and Ru−H bond paths (Figure 1b). The Ru−Zn bond critical point (BCP) metrics are typical for direct Ru−Zn bonds, [5] while the Ru−H BCP data are consistent with terminal Ru–hydrides. The computed Ru−H distances are 1.70 Å, as expected for a trans ‐HRuH moiety [7] .…”
Section: Methodsmentioning
confidence: 97%
“…In contrast to the clean activation of H 2 by complexes A-D, we recently showed that exposure of [Ru(PPh 3 )-(Ph 2 PC 6 H 4 ) 2 (ZnMe) 2 ] to H 2 gave an inseparable mixture of species. [5] When the reaction was repeated in the presence of 10 equiv of ZnMe 2 , [Ru(PPh 3 ) 2 (ZnMe) 4 H 2 ] (1 a) was formed as the major metal-containing product, albeit over ca. The product exhibited a symmetrical structure (Figure 1a) with four ZnMe groups in the equatorial plane (RuÀ Zn = 2.4564(3)-2.4664(2) Å) and two axial PPh 3 groups (RuÀ P = 2.3209(5), 2.3210(5) Å).…”
mentioning
confidence: 99%
“…In addition, the Ru–Zn heterobimetallic complex 56 was found to react with organozinc species constructing trimetallic [RuZn 2 ] complexes 80 and 82 (Scheme 27). 45,54 Their molecular structures revealed direct Ru–Zn bonds, discrete Zn–Me ligands and weak Zn⋯Zn interactions (2.59 and 2.68 Å). Moreover, the reaction of 80 with P n Bu 3 generated the ligand exchange product 81 , keeping the [RuZnZnMe] moiety intact.…”
Section: Reactivities Of Heterometallic Complexes Containing Mg- or Z...mentioning
confidence: 99%